FRI0202 SHORT AND LONG-TERM FOLLOW-UP OF APREMILAST THERAPY IN REFRACTORY SKIN LUPUS LESIONS. (June 2019) - Martín-Varillas, José Luis; Atienza-Mateo, Belén; Loricera, J.; Armesto, Susana; Cuende, Eduardo; Alegre-Sancho, Juanjo J.; Moriano, Clara; Calvo-Río, Vanesa; Calderón-Goercke, Monica; Prieto-Peña, D.; Bilbao, Lara Sánchez; González-Mazón, Iñigo; et al.
Abstract : Background: Treatment of skin lupus lesions (SLL) was based on topical therapy (corticosteroids, calcineurin inhibitors), systemic corticosteroids, antimalarials and immunomodulatory drugs including thalidomide. However, there are refractory patients to conventional treatment. Apremilast, an inhibitor of phosphodiesterase-4 (PDE-4), may be useful in these cases. Objectives: Our objective was to assess the efficacy and safety of apremilast. Methods: We set up an observational study of 8 patients with diagnosis of refractory SLL and treatment with apremilast at a standard dose of 30 mg/ 12 hours. The outcome was the presence of improvement and the appearance of side effects. Results: 8 patients (7 female/1 male) with mean age of 39.9±10.6 years with SLL were studied. Patients were diagnosed as follows: discoid lupus (n=5) and systemic lupus erythematosus (SLE) (n=3). Patients with SLE were classified as lupus panniculitis (n= 1), polycyclic ring lupus (n=1) and psoriasiform lupus (n=1). All skin lesions were confirmed by biopsy (table ). Before apremilast, all patients had received conventional therapy without improvement: topical corticosteroids (n=8), topical tacrolimus (n=4), oral corticosteroids (n=5), antimalarials (n=8), thalidomide (n=1), belimumab (n=3) and rituximab (n=2). The time between SLL diagnosis and apremilast beginning was 145.1±79.4 months. After a mean follow-up of 14.4±4.8 months, all patients presented improvement of skin lesions (4 of them with complete response). Due to the appearance of gastrointestinal symptoms (diarrhoea, vomiting) it was necessary to reduce the dose of apremilast to 30 mg/day in one patient and finally, it was discontinued due to no improvement with antiemetic and probiotic treatment. Conclusion: Apremilast seems useful and relatively safe in patients with refractory SLL to conventional treatment. Disclosure of Interests: José Luis Martín-Varillas: None declared, Belén Atienza-Mateo: None declared, J. Loricera: None declared, Susana Armesto: None declared, Eduardo Cuende: None declared, Juanjo J Alegre-Sancho: None declared, Clara Moriano: None declared, Vanesa Calvo-Río: None declared, Monica Calderón-Goercke: None declared, D. Prieto-Peña: None declared, Lara Sánchez Bilbao: None declared, Iñigo González-Mazón: None declared, C. González-Vela: None declared, J. Luis Hernández: None declared, Santos Castañeda Consultant for: Amgen, BMS, Pfizer, Lilly, MSD, Roche, Sanofi, UCB, Miguel A González-Gay Grant/research support from: Prof. MA Gonzalez-Gay received grants/research supports from Abbvie, MSD, Jansen and Roche., Speakers bureau: Consultation fees/participation in company sponsored speaker's bureau from Pfizer, Lilly, Sobi, Celgene, Novartis, Roche and Sanofi., Ricardo Blanco Grant/research support from: Abbvie, MSD, and Roche, Consultant for: Abbvie, Pfizer, Roche, Bristol-Myers, Janssen, Speakers bureau: Abbvie, Pfizer, Roche, Bristol-Myers, Janssen